Anabolic steroids in sport and exercise - Yesalis, Charles (Champaign, IL : Human Kinetics, 2000)
Anabolic Steroids in Sport and Exercise will give you an understanding of all aspects of steroid use and abuse as well as testing, treatment, and prevention options, plus insights from 15 experts on the scientific, clinical, historical, and legal aspects of steroid abuse and drug testing.
Part I. History and Incidence of UseChapter 1. Anabolic-Androgenic Steroids: A Historical Perspective and DefinitionCharles D. Kochakian and Charles E. Yesalis Endocrine Function of the Testis Androgens: Multiplicity of Male Hormones Anabolic Activity Partial Dissociation of Anabolic Activity From Androgenic Activity Anabolic Steroids Anabolic-Androgenic Steroids Therapeutic and Other Applications Veterinary Applications Summary ReferencesChapter 2. History of Anabolic Steroid Use in Sport and ExerciseCharles E. Yesalis, Stephen P. Courson, and James E. Wright Olympic Sports Female Athletes National Doping Programs Professional Football College High School Other Sports Conclusions ReferencesChapter 3. Incidence of Anabolic Steroid Use: A Discussion of Methodological IssuesCharles E. Yesalis, Michael S. Bahrke, Andrea N. Kopstein, and Camille K. Barsukiewicz Investigative Journalism Government Investigations Drug Testing Surveys Current Trends Methodological Issues Recommendations ReferencesChapter 4. Prevention of Anabolic Steroid UseLinn Goldberg and Diane L. Elliot Scope of the Problem Drug-Testing Policy Educational Strategies AS Education: The ATLAS Study The ATLAS Program Conclusions ReferencesPart II. Effects, Dependence, and Treatment IssuesChapter 5. Effect of Anabolic Steroid Use on Body Composition and Physical PerformanceKarl E. Friedl Variations in Physiological Response to Anabolic Steroids Comparing Anabolic Steroid Dose and Effects Empirical Strength Studies Composition of Steroid-Induced Body Weight Gain Body Composition Changes After Cessation of Anabolic Steroid Use Neuromuscular and Neuropsychological Effects of Anabolic Steroid Use Sustainment of Androgenicity During Demanding Physical Training Countermeasures for Stress-Induced Catabolic Hormones Improved Aerobic Endurance Performance Conclusions ReferencesChapter 6. Effects of Anabolic Steroids on Physical HealthKarl E. Friedl Distinctions Between Types and Doses of Anabolic Steroids Case Reports of Adverse Effects in Anabolic Steroid-Using Athletes Suspected Disease Associations Stroke: A New Association With Anabolic Steroids Prostate: An Androgen Target and Potential for Disease Musculoskeletal Injuries Problems Indirectly Associated With Anabolic Steroids Research on Health Effects Conclusions ReferencesChapter 7. Women and Anabolic SteroidsDiane L. Elliot and Linn Goldberg Normal Physiological Effects of Testosterone in Women and Men Prevalence of Anabolic Steroid Use in Females Physical Effects of Anabolic Steroids on Women Psychological Effects of Anabolic Steroids on Females DHEA: A Weak Androgen Physique-Altering Drug Use ReferencesChapter 8. Psychological Effects of Endogenous Testosterone and Anabolic-Androgenic SteroidsMichael S. Bahrke Anabolic Steroids and Aggressive Behavior in Animals Effect of Endogenous Testosterone Levels on Human Moods and Behaviors Estrogen-Related Aggression Contraceptive Studies and Moods Effects of Anabolic Steroids on Athletes' Moods and Behavior Effects of Anabolic Steroids on Psychological Dependence and Withdrawal Methodological Issues Conclusions ReferencesChapter 9. Anabolic Steroids: Potential for Physical and Psychological DependenceKirk J. Brower The Nature of Drug Abuse and Dependence Evidence for Dependence on Anabolic Steroids Mechanisms of Anabolic Steroid Dependence Predictors of Anabolic Steroid Dependence Course of Dependence on Anabolic Steroids Prevention and Treatment ReferencesChapter 10. Assessment and Treatment of Anabolic Steroid Abuse, Dependence, and WithdrawalKirk J. Brower Identification and Assessment Treatment of Withdrawal Conclusions ReferencesChapter 11. Legal Aspects of Anabolic Steroid Use and AbuseCarol Cole Kleinman and C.E. Petit Direct Legal Consequences of Steroid Abuse Indirect Legal Consequences of Steroid Abuse: Criminal Behavior The Proper Role of the Legal System Regarding Steroid Abuse ReferencesPart III. Testing and Societal AlternativesChapter 12. Evolution and Politics of Drug TestingJim Ferstle The Year of Scandals History of Drug Testing The Roots of Modern Drug Testing Challenges and Limitations in Drug Testing Causes for Criticism of Drug Testing Possible Solutions Outside the IOC Athletes' Rights in Drug Testing 1984: The L.A. Cover-Up More Secrets Testing Issues in Pro and U.S. Collegiate Sports Politics and Pharmacological Warfare Drug Testing and the Media ReferencesChapter 13. Drug Testing and Anabolic SteroidsR. Craig Kammerer Blood or Urine Testing? Structures, Chemistry, and Metabolism Technology of Anabolic Steroid Testing Philosophy of Anabolic Steroid Testing Costs of Anabolic Steroid Testing Circumventing Positive Test Results Use of Other Substances Future Directions in Anabolic Steroid Testing ReferencesChapter 14. Societal AlternativesCharles E. Yesalis, Michael S. Bahrke, and James E. Wright Legalization: An End to Hypocrisy? Interdiction: A Question of Cost-Effectiveness Education: Is Anybody Listening? Conclusion: Our Values Must Change References
Includes bibliographical references and index.
Keywords: Anabolic steroids -- Health aspects; Doping in sports